2019
DOI: 10.1002/jcla.22852
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and disease severity of Turkish FMF children carrying E148Q mutation

Abstract: BackgroundFamilial Mediterranean fever (FMF) is the most common hereditary monogenic autoinflammatory disease caused by mutations in the MEFV gene. It is controversial whether E148Q alteration is an insignificant variant or a disease‐causing mutation. The aim of this study was to evaluate the clinical features and disease severity of FMF patients carrying E148Q mutation.MethodsFiles of FMF patients were retrospectively evaluated. Patients with at least one E148Q mutation were included to the study. The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 25 publications
4
20
1
Order By: Relevance
“…Aydın et al reported that E148Q as a disease-causing mutation; they noted that patients with such mutation could present with late-onset and milder disease course and well response to colchicine as compared with patients who carry other mutations. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Aydın et al reported that E148Q as a disease-causing mutation; they noted that patients with such mutation could present with late-onset and milder disease course and well response to colchicine as compared with patients who carry other mutations. 39 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, there are studies that suggest that this variant is not benign and has at least some functional effect: There are multiple studies describing apparently typical FMF patients homozygous for p.Glu148Gln (Aydın et al, 2019;Topaloglu et al, 2005;Topaloglu et al, 2018 disease modifier of autoimmune disorders such as multiple sclerosis (Kümpfel et al, 2012), ulcerative colitis (Yıldırım et al, 2011), Crohn's disease (Karban et al, 2005), and rheumatoid arthritis (Rabinovich et al, 2005). It has also been associated with an increased risk for amyloidosis in autoimmune and in autoinflammatory disorders other than FMF (Aganna et al, 2004;Bunker & Gorevic, 2012).…”
Section: Patient Cohortmentioning
confidence: 99%
“…Aydin et al demonstrated that E148Q mutation is associated with a milder disease course, despite patients may have similar clinical ndings and well response to colchicine therapy, when compared to patients with other mutations [23]. In our case, the patient presented recurrent fever episodes associated to abdominal, chest pain, and arthralgia and presented a good response to colchicine treatment.…”
Section: Discussionmentioning
confidence: 45%